2001
DOI: 10.1051/0004-6361:20010794
|View full text |Cite
|
Sign up to set email alerts
|

V 1162 Ori: A multiperiodicδScuti star with variable period and amplitude

Abstract: Abstract. We present the results of multisite observations of the δ Scuti star V 1162 Ori. The observations were done in the period October 1999 -May 2000, when 18 telescopes at 15 observatories were used to collect 253 light extrema during a total of 290 hours of time-series observations. The purpose of the observations was to investigate amplitude and period variability previously observed in this star, and to search for low-amplitude frequencies. We detect, apart from the main frequency and its two first ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 15 publications
7
32
2
Order By: Relevance
“…1 and de-noised following the method used for XX Pyx by Handler et al (2000), it is possibly caused by intrinsic low frequencies or binarity as shown by Arentoft et al (2001a). We have noted a similar sinusoidal amplitude variation appearing in the δ Sct star V1162 Ori (Arentoft et al 2001b), for which binarity (Arentoft & Sterken 2000) and multiperiodicity were proposed and well discussed. Last, however, larger errors for the earlier values should be noted before giving any convincing explanations.…”
mentioning
confidence: 56%
“…1 and de-noised following the method used for XX Pyx by Handler et al (2000), it is possibly caused by intrinsic low frequencies or binarity as shown by Arentoft et al (2001a). We have noted a similar sinusoidal amplitude variation appearing in the δ Sct star V1162 Ori (Arentoft et al 2001b), for which binarity (Arentoft & Sterken 2000) and multiperiodicity were proposed and well discussed. Last, however, larger errors for the earlier values should be noted before giving any convincing explanations.…”
mentioning
confidence: 56%
“…Rodríguez et al (1997) confirmed that the amplitude of the main frequency of AN Lyn varies on a long time scale of several years, and changes in the amplitude are also present in the secondary frequencies. Arentoft et al (2001aArentoft et al ( , 2001b investigated the interesting medium amplitude δ Scuti star V1162 Ori and arrived at the remarkable result that the amplitude of the main frequency varies in a very complex way. Irregular variations are superimposed on a cyclic variation.…”
Section: Amplitudesmentioning
confidence: 99%
“…The variability may increase by ∼40 per cent over a decade. It was also shown that the light curve of the medium amplitude δ Scuti stars AN Lyn (Rodríguez et al 1997) and V1162 Ori (Arentoft et al 2001a(Arentoft et al , 2001b) underwent amplitude changes. The HADS may also be characterized by amplitude changes (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…There are relatively few discussions in the literature of observations of large amplitude, non-evolutionary period changes. In addition to the case already discussed of XX Pyx, period variations in V1162 Ori are presented by Arentoft et al (2001), and the peculiar behavior the one-time monoperiodic HADS star RY Lep is discussed by Laney & Schwendiman (2002). In both cases, changes in periodicity, similar in magnitude to those presented here, are found.…”
Section: Discussionmentioning
confidence: 91%